Considerations for STI Clinics During the COVID-19 Pandemic. Issue 7 (July 2020) - Napoleon, Siena C.; Maynard, Michaela A.; Almonte, Alexi; Cormier, Kevin; Bertrand, Thomas; Ard, Kevin L.; Chan, Philip A.
Abstract : Abstract: Coronavirus disease (COVID-19) is responsible for a global pandemic. It is important to balance the need for access to healthcare services, including testing and treatment for sexually transmitted infections. Sexually transmitted infection programs must consider how to use limited resources and implement novel approaches to provide continued access to care. Abstract : During the COVID-19 global pandemic, it is critical to preserve access to sexually transmitted infection care and treatment. Infection-control approaches should be utilized to minimize the risk to patients while maintaining access to important services.